2005
DOI: 10.1007/s00204-005-0034-4
|View full text |Cite
|
Sign up to set email alerts
|

Absence of liver tumor-initiating activity of kojic acid in mice

Abstract: In order to evaluate the tumor-initiating activity of kojic acid (KA) in mouse liver, an in vivo initiation assay in liver was performed using partially hepatectomized mice. Male ICR mice were fed on a basal diet (BD) containing 0 or 3% KA for 4 weeks, followed by distilled water (DW) containing 0 or 500 ppm phenobarbital (PB) for 13 weeks. Two weeks after the treatment with PB, two-thirds partial hepatectomy was preformed in all mice in order to enhance the regeneration and proliferating activities of the hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…As a result, no tumor-initiating activity was observed following a single oral administration of 2,000 mg/kg of KA and the dietary administration of 2% KA for 28 days [52]. In the latter assay using ICR mice, treatment with diet containing 3% KA for 4 weeks also did not show any tumor-initiating activity [31]. From these results, the possibility that KA has an in vivo genotoxic potential is considered to be extremely low, although KA has a tumor-promoting activity in the liver of rodent species.…”
mentioning
confidence: 92%
“…As a result, no tumor-initiating activity was observed following a single oral administration of 2,000 mg/kg of KA and the dietary administration of 2% KA for 28 days [52]. In the latter assay using ICR mice, treatment with diet containing 3% KA for 4 weeks also did not show any tumor-initiating activity [31]. From these results, the possibility that KA has an in vivo genotoxic potential is considered to be extremely low, although KA has a tumor-promoting activity in the liver of rodent species.…”
mentioning
confidence: 92%
“…From these findings, the authors reported that KA has neither liver initiation activity nor capability of 8-OxodG formation. In addition, KA did not exert initiation activity in mouse liver in the tumor initiation test (Moto et al, 2006). In this report, the authors noted that all the studies performed in mouse or rat livers until now suggested possible KA tumorpromotion activity, and it is speculated that the carcinogenic potential of KA is related to tumor-promoting activity more closely than tumor-initiating activity.…”
Section: Genotoxicity and Carcinogenicity Of Ka In Rat Livermentioning
confidence: 88%
“…During preparation of this manuscript it has been reported in a two step carcinogenesis study, in which mice were fed a diet containing 3z KA at initiation step and phenobarbital was used as a tumor promoter, that there is no liver tumor initiating activity (19). At present, it is not clear whether the partial hepatectomy which was performed two weeks after the beginning of phenobarbital administration was at an appropriate time to detect initiating activity of KA or not.…”
Section: Discussionmentioning
confidence: 99%